2018
DOI: 10.1021/acsphotonics.7b01159
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Optical Amplification in the Nanosecond Regime from Formamidinium Lead Iodide Nanocrystals

Abstract: Lead halide perovskite nanocrystals (NCs) were recently found to exhibit extraordinary optical amplification properties. The great majority of such studies implemented ultrashort photon pulses in the femtosecond regime to initiate the stimulated emission process. Yet the realization of practical lasing applications based on such materials is crucially dependent on their ability to sustain optical amplification at significantly longer time scales, at which major losses associated with spontaneous emission and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 57 publications
5
26
0
Order By: Relevance
“…In a further experiment [33], FAPbI 3 and FA 0.1 Cs 0.9 PbI 3 NCs were synthesized, characterized by high PLQY and efficient ASE spanning the red and near infrared range. Efficient optical amplification in the nanosecond regime in FAPbI 3 NCs films was also demonstrated by Papagiorgis et al [34] that obtained room temperature ASE with a minimum threshold of 140 µJcm −2 in films annealed at 90 • , under 4 ns pumping at 532 nm, while no ASE was observed in as-deposited films. Further improvements of the NCs stability during purification were obtained by Krieg et al [35] that synthesized CsPbBr 3 NCs capped with zwitterionic long-chain molecules.…”
Section: Perovskites Nanocrystals Thin Filmssupporting
confidence: 52%
“…In a further experiment [33], FAPbI 3 and FA 0.1 Cs 0.9 PbI 3 NCs were synthesized, characterized by high PLQY and efficient ASE spanning the red and near infrared range. Efficient optical amplification in the nanosecond regime in FAPbI 3 NCs films was also demonstrated by Papagiorgis et al [34] that obtained room temperature ASE with a minimum threshold of 140 µJcm −2 in films annealed at 90 • , under 4 ns pumping at 532 nm, while no ASE was observed in as-deposited films. Further improvements of the NCs stability during purification were obtained by Krieg et al [35] that synthesized CsPbBr 3 NCs capped with zwitterionic long-chain molecules.…”
Section: Perovskites Nanocrystals Thin Filmssupporting
confidence: 52%
“…It is reasonable to assume that the NC agglomeration effects become increasingly pronounced as NC concentration increases. NC aggregation is consistent with the broadening and red-shift of the band-edge due to the loss of confinement and the decrease of the PL quantum yield and lifetime due to increased non-radiative recombination, as merging of the NCs is known to lead to exciton quenching effects (Stadler et al, 2015; Papagiorgis et al, 2018).…”
Section: Resultssupporting
confidence: 62%
“…It has been demonstrated that metal-lead halide perovskites exhibit good light amplification emission. Evidence of high optical gains and efficient amplified spontaneous emissions (ASE) is reported for bulk polycrystalline thin films of organic- inorganic [ 29 , 31 , 109 , 110 ] and fully inorganic perovskites [ 33 , 35 ] and for perovskite nanocrystal films [ 16 , 38 , 111 , 112 , 113 , 114 ].…”
Section: Perspectivesmentioning
confidence: 99%